2019
DOI: 10.1186/s12935-019-1077-6
|View full text |Cite
|
Sign up to set email alerts
|

RAD51 is a potential marker for prognosis and regulates cell proliferation in pancreatic cancer

Abstract: BackgroundThe DNA damage and repair pathway is considered a promising target for developing strategies against cancer. RAD51, also known as RECA, is a recombinase that performs the critical step in homologous recombination. RAD51 has recently received considerable attention due to its function in tumor progression and its decisive role in tumor resistance to chemotherapy. However, its role in pancreatic cancer has seldom been investigated. In this report, we provide evidence that RAD51, regulated by KRAS, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…VEGF promotes tumor angiogenesis and is associated with endothelial radiosensitization ( 3 ). Similarly, activated ERK increases RAD51 expression in pancreatic cancer cells ( 44 ), which promotes homologous DNA repair, leading to RT resistance ( 45 ). In addition, a recent study determined that γ-ray irradiation alone can increase cell migration in vitro , which is mainly achieved by activating the EGFR/ERK/AKT signaling pathway and increasing the expression of nuclear factor γB (NFγB) ( 46 ).…”
Section: Erk and Irradiated Cancer Cellsmentioning
confidence: 99%
“…VEGF promotes tumor angiogenesis and is associated with endothelial radiosensitization ( 3 ). Similarly, activated ERK increases RAD51 expression in pancreatic cancer cells ( 44 ), which promotes homologous DNA repair, leading to RT resistance ( 45 ). In addition, a recent study determined that γ-ray irradiation alone can increase cell migration in vitro , which is mainly achieved by activating the EGFR/ERK/AKT signaling pathway and increasing the expression of nuclear factor γB (NFγB) ( 46 ).…”
Section: Erk and Irradiated Cancer Cellsmentioning
confidence: 99%
“…Introduction of Kras G12D mutation, a mutation frequently observed in PC, could increase mRNA and protein expression levels of RAD51 via MEK/ERK axis. RAD51 further promotes PC glycolysis via upregulation of HIF-1α transcriptional process [ 40 ]. Another study demonstrated that KRAS/MEK/ERK signaling exacerbates hypoxia-driven HIF-1α and HIF-2α protein stability in PDAC cells that express activated KRAS, followed by upregulation of downstream HIF-1α-induced effectors such as CA9 and monocarboxylate transporter (MCT) 4, leading to perturbation of pH regulation and metabolic rewiring toward a glycolytic phenotype [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of endogenous HIF-1α and HIF-2α reduces the LDHA expression even in hypoxic condition, accompanied with a significant decrease in glucose utilization and lactate production [ 50 ]. Compared to the elevated LDHA level [ 10 , 29 , 40 , 50 ], the expression of LDHB is suppressed and even lost in PC tissues due to hypermethylation of its promoter. Decreased expression of LDHB leads to glycolytic transition, while restored its expression leads to reduced LDH activity and lactate production but increases intracellular ATP concentration [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, 10 µL of the cell counting kit 8 (CCK‐8) solution was added for 2 hours of incubation. The absorbance value of each well at 450 nm was measured for plotting a growth curve 16,17 …”
Section: Methodsmentioning
confidence: 99%